Current and future trends in tuberculosis incidence in New York City: a dynamic modelling analysis - Dr Anthony T Fojo, MD; Natalie L Stennis, MPH; Andrew S Azman, PhD; Emily A Kendall, MD; Sourya Shrestha, PhD; Shama D Ahuja, PhD; David W Dowdy, MD (Elsevier, 2017)
Background: After steady decline since the 1990s, tuberculosis incidence in New York City and throughout the USA has plateaued. We aimed to explore the major drivers of the flattening of tuberculosis incidence in New York City and to project the future trajectory of the tuberculosis epidemic in the absence of any additional intervention. Methods: We developed a compartmental transmission model of tuberculosis in New York City. The model was parameterised with detailed epidemiological data and stratified by age and nativity (US-born vs foreign-born). We ran the model under five alternative scenarios representing different explanations for recent declines in tuberculosis incidence. We evaluated the relative likelihood of each scenario by comparing its output with available data. We used the most likely scenarios to explore potential mechanisms underlying the recent declines in tuberculosis in New York City and to describe the reasonable range of future epidemic trajectories. Our primary outcome was the projected rate of decline in tuberculosis incidence from 2015 to 2025. Model calibration yielded estimates of future disease incidence and reductions in incidence with 95% credible intervals (CrIs). Findings: Demographic changes and declining tuberculosis transmission alone were insufficient to explain recent trends in tuberculosis incidence in New York City. Only scenarios that assumed contemporary changes in tuberculosis dynamics among foreign-born individuals-a declining rate of reactivation or a decrease in imported subclinical tuberculosis-could accurately describe the trajectory of disease incidence since 2007. In those scenarios, the projected decline in incidence from 2015 to 2025 varied from minimal (2·0% per year [95% CrI 0·4-3·5]) to similar to 2005 to 2009 trends (4·4% per year [2·5-6·4]). The primary factor differentiating optimistic from pessimistic projections was the degree to which improvements in tuberculosis dynamics among the foreign-born population continued into the coming decade. Interpretation: Further progress towards elimination of tuberculosis in New York City requires additional focus on the foreign-born population. Without additional intervention in this group, tuberculosis incidence might not decline further. Funding: None.